A Dramatic Response to Toripalimab With Chemotherapy and Antiangiogenic Agent Followed by Surgery in a Stage IIIB Lung Adenocarcinoma Patient With an Uncommon EGFR Mutation: A Case Report - Zhai, Pengda; Niu, Xueliang; Zheng, Kai (Frontiers in Oncology, 2022)
Lung cancer patients with high programmed cell death-ligand 1 (PD-L1) expression in tumor cells and epidermal growth factor receptor (EGFR) mutations are rare, but there is no clinical standard for which treatment such patients should receive. Here, we report a 52-year-old male smoker who was diagnosed with stage IIIB lung adenocarcinoma. A rare EGFR G719A mutation was detected in the lymph node samples by next-generation sequencing (NGS) and high PD-L1 expression was found by immunohistochemistry (IHC). After 10 cycles of induction therapy (toripalimab plus pemetrexed plus nedaplatin plus apatinib), surgery was successfully performed, followed by 2 cycles of consolidation therapy (toripalimab plus pemetrexed) and 4 cycles maintenance therapy (toripalimab). A progression-free survival (PFS) of 7 months was achieved. In this case, we showed that the programmed cell death protein 1 (PD-1) inhibitor toripalimab plus chemotherapy and apatinib was effective and tolerable in a local advanced EGFR-mutant NSCLC patient with positive PD-L1 expression.